2020
DOI: 10.1542/hpeds.2019-0270
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Circumcision on Exclusive Breastfeeding, Phototherapy, and Hospital Length of Stay in Term Breastfed Newborns

Abstract: BACKGROUND AND OBJECTIVES:Little is known about the effect of circumcision on breastfeeding in the hours and days after the procedure. Factors with the potential to negatively impact breastfeeding success in the newborn period may result in higher rates of jaundice requiring phototherapy and formula supplementation, both of which can potentially extend the length of initial hospitalization. Our objective was to determine the impact of circumcision on rates of exclusive breastfeeding, neonatal jaundice requirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Bottle‐feeding before and after NMC was also unaffected in a Michigan study 32 . A Connecticut study found no effect of NMC on exclusive breastfeeding or length of hospital stay 28 . A US mid‐west study found no significant difference in mother‐infant interactions for 43 discrete behaviors during 4 hospital feeding sessions comparing neonates randomized to receive NMC without anesthesia on day 2 postbirth and neonates whose NMC was delayed to day 3 33 .…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Bottle‐feeding before and after NMC was also unaffected in a Michigan study 32 . A Connecticut study found no effect of NMC on exclusive breastfeeding or length of hospital stay 28 . A US mid‐west study found no significant difference in mother‐infant interactions for 43 discrete behaviors during 4 hospital feeding sessions comparing neonates randomized to receive NMC without anesthesia on day 2 postbirth and neonates whose NMC was delayed to day 3 33 .…”
Section: Resultsmentioning
confidence: 93%
“…Figure 1 summarizes results of sequential searches in which articles already retrieved were not included again. Keyword combinations and articles meeting the inclusion criteria retrieved by PubMed searches were: “circumcision pain psychology,” 11,13–18 “circumcision trauma,” 19,20 “circumcision autism,” 21–24 “circumcision SIDS,” 25 “circumcision breastfeeding,” 26–29 “circumcision newborn.” 30–34 For EMBASE these were “circumcision pain,” 35,36 and “circumcision psychology.” 37 A SCOPUS search for “circumcision male psychology” found one further article 38 . The Cochrane Library search did not yield further articles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taddio et al demonstrated a stronger pain response to routine vaccination in infants circumcised without anesthesia in comparison with uncircumcised infants or circumcised babies treated with topical anesthesia; they argued that MC without anesthetic may induce changes in infant pain behavior because of alterations in the neural processing of painful stimuli [10]. By contrast, a recent analysis by O'Callahan et al demonstrated that newborns circumcised with proper analgesia (24%sucrose plus local anesthesia with lidocaine or DPNB and acetaminophen) showed no differences in the rate of exclusive breastfeeding during the initial hospitalization compared with non-circumcised newborns [45]. Therefore, it is imperative for clinicians to attempt all the possible strategies to reduce neonatal pain, and since MC is an invasive painful procedure, performing it without anesthesia appears to be contraindicated [8].…”
Section: Discussionmentioning
confidence: 97%